2021
DOI: 10.1177/09603271211008506
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Clinical study of the clinical characteristics and prognosis of 1219 cases of endometrial cancer with lymph node metastasis

Abstract: To analyze the clinical characteristics and prognosis of endometrial cancer patients with lymph node metastasis to provide a reference for lymphadenectomy in endometrial cancer. The data used in this study were extracted from a tertiary hospital in Guangxi, China based on the hospital information system. 1219 patients with endometrial malignancy who were treated in our hospital. The lymph node metastasis rate was 9.8%. The metastasis rate of the abdominal aorta + pelvic lymph nodes (56.7%) was significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Zhang et al analyzed 1219 cases of endometrial cancer, assessing their characteristics and their prognoses, as these were associated with lymph node metastasis. Their study revealed a higher rate of metastasis in paraaortic and pelvic nodes (56.7%) than pelvic alone (24.2%) or paraaortic alone (19.2%) [37]. There was a proportionally higher rate of metastasis in postmenopausal women than younger women.…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al analyzed 1219 cases of endometrial cancer, assessing their characteristics and their prognoses, as these were associated with lymph node metastasis. Their study revealed a higher rate of metastasis in paraaortic and pelvic nodes (56.7%) than pelvic alone (24.2%) or paraaortic alone (19.2%) [37]. There was a proportionally higher rate of metastasis in postmenopausal women than younger women.…”
Section: Discussionmentioning
confidence: 95%
“…Tumor invasion and metastasis include a series of events related to the interaction between tumor cells or between tumor cells and the microenvironment, including tumor cells separating from each other, migrating to the extracellular matrix and entering the blood and lymphatic vessels [ 24 ]. In the study of endometrial cancer that compared with patients without lymph node metastasis, some scholars found that the overall survival rate of patients with cervical invasion and lymph node vascular invasion was obviously decreased [ 25 ]. All these results indicated that it was important to evaluate the prognosis of patients with CC by judging the FIGO stage, differentiation degree, lymph node metastasis and INHBA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Toole et al reported that CA125 could be used as a preoperative risk stratification factor for lymph node metastasis of endometrioid cancer and was significantly correlated with lymph node metastasis [ 36 ]. Li et al also found that the proportion of lymph node metastasis in EC patients with CA125 ≥ 35 U/ml was higher than that in patients with CA125 < 35 U/ml [ 37 ]. The results of our study showed that CA125 was higher in TP53mut patients, which may be due to the higher lymph node metastasis rate in patients with TP53mut (21/22, 95.5%).…”
Section: Discussionmentioning
confidence: 99%